The quantitative and qualitative bacteriological analysis of the Manhattan city water - Cooper, Katherine (My University, 1908)
Introduction: It has only been within the past few years that scientists have discovered the value of bacteriological examination of drinking water. There have been terrible epidemics of water borne contagious diseases, but only since the advent of bacteriology has it been known how these diseases were spread.
Citation: Cooper, Katherine. The quantitative and qualitative bacteriological analysis of the Manhattan city water. Senior thesis, Kansas State Agricultural College, 1908.
Keywords: Water; Kansas; Pathogenesis; Bacteria; Graduating theses; Senior theses; Theses